Comparison of Silver and Aluminum Patches on the Electromagnetic Radiation of a Microstrip Dipole Antenna - Aslam Chitami Priawan Siregar; Aprilia Dewi Ardiyanti; Ni’matut Tamimah (Faraday: Journal of Fundamental Physics, Research, and Applied Science, 2026)
This paper compares silver (Ag) and aluminum (Al) as patch materials for a microstrip dipole antenna to examine how their electrical conductivities affect electromagnetic radiation performance. Both antennas were designed with identical geometrical and substrate parameters using the Finite-Difference Time-Domain (FDTD) method, varying only the patch material. Simulation results show that the resonant frequencies are 2.4700 GHz for Ag and 2.4649 GHz for Al, with excellent VSWR values 1.0839 and 1.0836 and return loss below –27 dB. Both materials exhibit reflected power below 0.2% and have nearly identical radiated power, namely 0.3647 W for silver (Ag) and 0.3646 W for aluminum (Al). Overall, silver and aluminum demonstrate almost identical radiation characteristics. Silver offers slightly better conductivity, while aluminum provides similar efficiency at lower cost, making it a practical alternative for lightweight and economical microstrip antenna applications.